AB0985 Clinical Characteristics and Mortality of Our Patients Admitted To ICU. (15th July 2016) - Garcia Vadillo, A.; Garcia-Lorenzo, E.; Rodriguez-Serrano, D.A.; Llorente, I.; Merino, L.; Lopez-Bote, J.P.; Lopez-Fernandez, M.I.; Gonzalez-Alvaro, I.
Abstract : Objectives: To determine the characteristics and mortality of patients with inflammatory rheumatic diseases admitted to intensive care unit (ICU). Methods: We present a retrospective observational study including all patients with inflammatory rheumatic diseases admitted to the ICU of a tertiary hospital in Madrid from January 2004 to December 2014. We excluded all those with stay of less than 24 hours in this unit. Patients who were readmitted to ICU during the same hospital admission were considered as a single entry. We retrospectively collected several characteristics of the diseases, including biological activity, and also treatments received for the three months before admission to the ICU. Statistical analysis was performed using Stata 12.1. Results: A total population of 56 patients required 62 income in ICU (6 of them required 2 consecutive admissions). The mean age was 58.6 ±14 years. 55% were women. 41% of patients (23) had systemic vasculitis, 7 of them ANCA positive. 28.5% (16) suffered connective tissue disease: 10 spondylitis, 3 rheumatoid arthritis and 4 other different processes. The average from diagnosis until their first ICU admission was 127± 176 months. 67% of patients had previously been treated with glucocorticoids for an average of 13 months at a dose of 7 mg (p50) prednisone/day. 14% of patients had received boluses of glucocorticoids, 20% biologic therapies and 18% cyclophosphamide. 63% showed signs of disease activity at the time of entering the ICU. At ICU admission APACHE II severity index was p50: 20 (p25-p75: 13.5–26) and p50 SAPSII: 34.5 (p25-p75: 24–43). The most common causes were respiratory failure (58% of episodes) and septic shock (14.5%). During their stay in ICU 79% of patients required glucocorticoids, 35% received boluses of glucocorticoids, 20% cyclophosphamide and 11% plasmapheresis. 41 patients (68%) required mechanical ventilation, being invasive in 38. The mean ICU stay was 15.8 ±14 days. 28.5% (16) patients died during their stay in this unit, and 11% (7 patients) died in the hospital after leaving the ICU. Deaths was significantly associated with age (OR: 1.09 annually), elderly (OR: 7.52 for patients >70 compared to those <45) female sex (OR 3.7), APACHE II (OR: 1.15 per unit increased) and iv administration of gamma globulins in ICU (OR: 16.6) in multivariate analysis. Conclusions: Vasculitis and connective tissue diseases are the main inflammatory rheumatic diseases that require our patients to ICU admission. At the time of these they have high rates of disease gravity. Mortality was associated with advanced age, elderly, female sex, severity measured by APACHE II and also with the need of gamma globulin iv administration. Disclosure of Interest: None declared